Empirische Analyse des Offenlegungszeitpunkts von Jahresabschlüssen nach dem EHUG - Henselmann, Klaus; Kaya, Devrimi (2008)
The paper analyses the timing of disclosing financial statements for small and medium enterprises (SME) in Germany in 2007 and 2008. Comparisons of different regional areas and different company sizes are made and possible explanations for the results discussed. – Rechnungslegungspolitik ; Publizitätsverhalten ; Größenklassen ; Kleine und Mittlere Unternehmen (KMU) ; Elektronisches Unternehmensregister